2005
DOI: 10.1681/asn.2005020176
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fish Oil Supplementation on Kidney Transplantation

Abstract: The objective of this study was to assess the effects of omega-3 fatty acid supplementation on various kidney transplantrelated outcomes. A systematic review and meta-analysis was performed of published randomized, controlled trials (RCT). There were 16 kidney transplant RCT with a total of 812 patients. All trials evaluated fish oil with dosages that ranged from 1.2 to 5.4 g/d. No consistent benefits were observed for any outcome with the exception of a modest benefit on triglycerides. A meta-analysis of reje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 24 publications
3
34
1
Order By: Relevance
“…28,29 Although renal function improved after marine n-3 FA supplementation in some studies, most trials reported a nonsignificant increase in Δ mGFR of 3-5 mL/ TA B L E 3 Effects of marine n-3 FA supplementation on change in cardiovascular endpoints during follow-up Lower respiratory tract infection 8 6 28,29 Although renal function improved after marine n-3 FA supplementation in some studies, most trials reported a nonsignificant increase in Δ mGFR of 3-5 mL/ TA B L E 3 Effects of marine n-3 FA supplementation on change in cardiovascular endpoints during follow-up Lower respiratory tract infection 8 6…”
Section: Discussionmentioning
confidence: 99%
“…28,29 Although renal function improved after marine n-3 FA supplementation in some studies, most trials reported a nonsignificant increase in Δ mGFR of 3-5 mL/ TA B L E 3 Effects of marine n-3 FA supplementation on change in cardiovascular endpoints during follow-up Lower respiratory tract infection 8 6 28,29 Although renal function improved after marine n-3 FA supplementation in some studies, most trials reported a nonsignificant increase in Δ mGFR of 3-5 mL/ TA B L E 3 Effects of marine n-3 FA supplementation on change in cardiovascular endpoints during follow-up Lower respiratory tract infection 8 6…”
Section: Discussionmentioning
confidence: 99%
“…Three separate meta-analyses of RCTs focusing on the effect of marine n-3 PUFA supplementation after renal transplantation have reported a significant reduction in triglyceride levels, a minor reduction of diastolic BP, and slightly increased concentrations of HDL cholesterol, with possible beneficial effect on patient survival (19)(20)(21). However, effects on mortality rates could not be evaluated because of a low number of events (only seven deaths in 846 patients) and short follow-up (19,21).…”
Section: Discussionmentioning
confidence: 99%
“…In RTRs, there have been reports of improved renal function with marine n-3 PUFA supplementation (29). Most studies, however, reported no effect (19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the encouraging results of some studies [18], 2 recent metanalyses did not find strong enough evidence to conclude that n-3 PUFAs could prevent acute graft rejections, increase graft survival, or improve renal function [36,37]. Part of the inconsistencies in the literature could be due to the low compliance to treatment observed in patients receiving PUFAs supplementation.…”
Section: Good Patient Compliance To the N-3-rich Dietmentioning
confidence: 99%